Churches and charity in the immigrant city: religion, immigration, and civic engagement in Miami - Stepick, Alex; Rey, Terry; Mahler, Sarah J. (Rutgers University Press, 2009)
Religion, immigration, and civic engagement / Alex Stepick, Terry Rey, Sarah J. Mahler -- So close and yet so far away: comparing civic social capital in two Cuban congregations / Sarah J. Mahler -- Refugee Catholicism in Little Haiti: Miami's Notre Dame d'Haiti Catholic Church / Terry Rey, Alex Stepick -- Politics and prayer in West Perrine: civic engagement in the Black church / Su Oltman Fink -- Unidos en la Fe: transnational civic social engagement between two Cuban Catholic parishes / Katrin Hansing -- La Catedral del Exilio: a Nicaraguan congregation in a Cuban church / Isabel del Pino-Allen -- Black churches and the environment in Miami / Eileen M. Smith-Cavros -- Youth and charity in a Sweetwater Parish: Our Lady of Divine Providence Church / Aidil Oscariz -- Faith in the fields: Mexican Marianism in Miami-Dade County / Noemí Báez ... [et al.] -- The struggle for civic social capital in West Indian churches / Teruyuki Tsuji, Christine Ho, Alex Stepick -- Religious practice and civic social capital among Miami youth / Yves Labissiere, Ann Reeder Goraczko, Alex Stepick -- Conclusions: religious leadership and civic social capital / Alex Stepick, Sarah J. Mahler, Terry Rey